Thermodynamic Insights into the Separation of Carotenoids in Reversed-Phase Liquid Chromatography - Nicola Marchetti; Pier Paolo Giovannini; Martina Catani; Luisa Pasti; Alberto Cavazzini (International Journal of Analytical Chemistry)
The retention mechanism of four major carotenoids, two xanthophylls (i.e., lutein and zeaxanthin) and two carotenes (i.e., lycopene and β-carotene), was investigated in reversed-phase liquid chromatography with the aim of thermodynamic analysis. The experimental variables considered in this study were the composition of mobile phase (MP) and the temperature. Chromatographic elutions were undertaken under linear, isocratic conditions by using a C18 stationary phase, four different MP compositions (by varying the ratio methanol/acetonitrile from 66.5/28.5 to 47.5/47.5 v/v), and column temperatures in the range 283–313 K. Traditional Van’t Hoff analysis has been used to estimate changes of standard enthalpy (ΔH∘) and Gibbs free energy (ΔG∘) associated with the solute transfer from the mobile to the stationary phase at each mobile phase composition. The thermodynamic quantities have been correlated to the structure of investigated carotenoids and their interaction with the octadecyl silica stationary phase.